2002
DOI: 10.1121/1.1501277
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear model of thermoacoustic devices

Abstract: This paper presents a nonlinear, time-domain model of thermoacoustic devices based on cross-sectional averaged equations. Heat transfer perpendicular to the device axis--which lies at the core of thermoacoustic effects--is modeled in a novel and more realistic way. Heat conduction in the solid surfaces surrounding the fluid medium is included. Contrary to the previous versions of this model [Watanabe et al., J. Acoust. Soc. Am. 102, 3484-3496 (1997)], the present version does not require artificial damping and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…That is the reason why the development of adequate simulation tools is still needed to describe the evolution of acoustic wave amplitude after the onset of thermoacoustic instability. On the one hand, direct numerical simulation [12][13][14][15] seems to be the only way to reproduce quantitatively the effects mentioned above, but it is still limited by large computation times inherent to the complicated physics and the multiple time and space scales involved in the description of thermoacoustic engines. On the other hand, analytical models are often based on substantial approximations, but one can be motivated by the development of some phenomenological approach aiming at reproducing qualitatively the experiments in order to get deeper understanding of the operation of thermoacoustic engines.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…That is the reason why the development of adequate simulation tools is still needed to describe the evolution of acoustic wave amplitude after the onset of thermoacoustic instability. On the one hand, direct numerical simulation [12][13][14][15] seems to be the only way to reproduce quantitatively the effects mentioned above, but it is still limited by large computation times inherent to the complicated physics and the multiple time and space scales involved in the description of thermoacoustic engines. On the other hand, analytical models are often based on substantial approximations, but one can be motivated by the development of some phenomenological approach aiming at reproducing qualitatively the experiments in order to get deeper understanding of the operation of thermoacoustic engines.…”
Section: Introductionmentioning
confidence: 98%
“…They took into account the influence of various nonlinear effects such as minor losses at the edges of the stack, higher harmonics generation, heat pumping by acoustic waves, and heat convection by the so-called Gedeon streaming [20]. It is worth noting that only a few papers [9,13,14,19] provide direct comparisons of calculated transient regimes with experimental data, and to our knowledge, most of the complicated effects mentioned above cannot be reproduced by the models, even for the simplest thermoacoustic oscillators which can be built, like the Sondhaus tube or the socalled thermoacoustic laser [21].…”
Section: Introductionmentioning
confidence: 99%
“…Models relying on this approximation neglect the contribution of longitudinal gradients of temperature oscillations to the convective heat flux along the stack. However, when longitudinal gradients of temperature oscillations are not neglected, analytical models by Gusev et al [9,10] and numerical models by Karpov and Prosperetti [12] showed that, near the ends of a thermoacoustic stack, the thermal field is nonlinear. This was further validated by direct numerical simulations [7,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…(1c), because we have added an extra term corresponding to axial conduction. As stated by Karpov et al, 9 this term is only important near walls. The reason for adding this term is explained in Appendix A.…”
Section: B Application Of the Nlfd Methodsmentioning
confidence: 78%